State of enzyme systems of polymorphonuclear leukocytes by the gingival margin level correction - M. V. Goman; I. A. Zaborovets; Yu. N. Mayboroda (Кубанский научный медицинский вестник, 2015)
The paper deals with the results of cytochemical studies of biologically active enzyme systems of neutrophilic granulocytes and their comparative analysis to assess the effectiveness of gingiva preparation and scalpel use for the correction of the gingival margin. A detailed study of biologically active substances in dynamics in the peripheral blood neutrophils with differentiated definition of cell populations showed no clear difference of cell diversity and excess of content and activity of enzymes of oxidoreductases and hydrolases groups in comparing the effectiveness of gingiva preparation or scalpel use. Asynchronous oscillations of hydrolase activity at gingiva preparation cause a decrease of metabolic processes in the field of surgery.